1991
DOI: 10.1063/1.460137
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of low-lying electronic states of aminonitrene, phosphinonitrene, and phosphinocarbene

Abstract: A theoretical study of the electronic structure and spectroscopic properties of the low-lying electronic states of the molecule SiB A theoretical investigation of some lowlying electronic states of imidazoleThe recently formulated multiconfiguration-based unitary coupled electron pair approximation (UCEPA) is compared with muItireference configuration interaction (MR-CISD) calculations, including all single and double excitations, for the molecules in this study. The electronic states of the molecules in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This reaction yields three products, viz., N 2 , cyanamide, and 1,1-diazine (Figure ). Note that such process is very specific for DAT in comparison with other 1-substituted tetrazoles due to enhanced stabilization of 1,1-diazine, which is a singlet aminonitrene, in comparison with similar simple singlet nitrenes (e.g., :NH or :N–CH 3 ). , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction yields three products, viz., N 2 , cyanamide, and 1,1-diazine (Figure ). Note that such process is very specific for DAT in comparison with other 1-substituted tetrazoles due to enhanced stabilization of 1,1-diazine, which is a singlet aminonitrene, in comparison with similar simple singlet nitrenes (e.g., :NH or :N–CH 3 ). , …”
Section: Resultsmentioning
confidence: 99%
“…Note that such process is very specific for DAT in comparison with other 1substituted tetrazoles due to enhanced stabilization of 1,1diazine, which is a singlet aminonitrene, in comparison with similar simple singlet nitrenes (e.g., :NH or :N−CH 3 ). 52,53 The elimination of azide NH 2 N 3 (TS3, Figure 4, left side) is ∼10 kcal mol −1 higher than the primary channel (Scheme 4). Although the former reaction has been scrutinized in detail in a recent computational work, 29 it turned out to be entirely unimportant kinetically.…”
Section: Mutual Interconversion Of Dat Isomersmentioning
confidence: 99%
“…This finding is consistent with the trend observed in previous ab initio studies. [31] It was previously postulated that Int1A may also undergo a rebound to form a N-hydroxyl intermediate (Intermediate 2 in Scheme 1). [22] However, our attempts to identify the pathway connecting Int1A and In- termediate 2 were unsuccessful, and we found that a N-hydroxyl intermediate was obtained only on Path B (Int2B).…”
Section: Resultsmentioning
confidence: 99%
“…Similar conclusions can be drawn from the X-ray crystal structure analysis of the phosphinosilylcarbene XIg (Figure 12), 82 the silyl group playing the same role as the phosphonio group of XIIa. The Si2N2C3N1C2P1C1Si1 skeleton is planar (maximum The first study by Hegarty and co-workers 84 concluded that the parent phosphinocarbene H 2 PCH XIg* has a singlet ground state, with a singlettriplet gap of 3 kcal/mol, while later on Hoffmann and Kuhler 85 predicted a somewhat larger gap (6.7 kcal/ mol) using a more sophisticated level of theory. Together, the planar geometry of the singlet state and the shortness of the PC bond (1.616 Å) confirm the strong interaction of the phosphorus lone pair with the vacant orbital of the carbene center.…”
Section: Iv31 Phosphinosilyl-and Phosphinophosphoniocarbenesmentioning
confidence: 99%
“…The first study by Hegarty and co-workers concluded that the parent phosphinocarbene H 2 PCH XIg* has a singlet ground state, with a singlet−triplet gap of 3 kcal/mol, while later on Hoffmann and Kuhler predicted a somewhat larger gap (6.7 kcal/mol) using a more sophisticated level of theory. Together, the planar geometry of the singlet state and the shortness of the PC bond (1.616 Å) confirm the strong interaction of the phosphorus lone pair with the vacant orbital of the carbene center.…”
Section: Iv3 (Xz)-carbenesiv31 Phosphinosilyl- and Phosphinophosphoni...mentioning
confidence: 99%